2023
DOI: 10.1017/jns.2023.19
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and anaemia among Indian adolescents: role of dietary diversity and hygiene practices

Abstract: In 2021, the Lancet Commission on adolescent nutrition highlighted the need to prioritise the elimination of adolescent malnutrition to tap the human capital potential and break the intergenerational malnutrition trap. The nutritional requirement during adolescence reaches its peak. The present study aims to appraise the prevalence of undernutrition (stunting and thinness) and anaemia among adolescents (10–19 years) in India and the role of socioeconomic, individual-level hygiene behaviour and dietary diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…This study revealed that being a follower of Orthodox and Muslim religions increases stunting as compared to those who are protestant. This finding is in line with the study conducted in India and Ethiopia [ 32 , 33 ]. This difference could be attributed to dietary restrictions imposed by Orthodox Christianity, such as fasting periods that may limit nutrient intake during critical growth periods.…”
Section: Discussionsupporting
confidence: 93%
“…This study revealed that being a follower of Orthodox and Muslim religions increases stunting as compared to those who are protestant. This finding is in line with the study conducted in India and Ethiopia [ 32 , 33 ]. This difference could be attributed to dietary restrictions imposed by Orthodox Christianity, such as fasting periods that may limit nutrient intake during critical growth periods.…”
Section: Discussionsupporting
confidence: 93%
“…Due to the unwillingness of WASH practice a large amount of people specially the children suffer from many diseases such as diarrhoea in Southeast Nigeria 7 . Stunting and anaemia among adolescents in India are significantly predicted by dietary variety and cleanliness practices 8 . WASH behaviors are most effective in the early years when it comes to improving children's long‐term health 9 .…”
Section: Introductionmentioning
confidence: 99%
“… 7 Stunting and anaemia among adolescents in India are significantly predicted by dietary variety and cleanliness practices. 8 WASH behaviors are most effective in the early years when it comes to improving children's long‐term health. 9 In some rural residents of Ethiopia have limited access to basic water utilities.…”
Section: Introductionmentioning
confidence: 99%
“…The study highlights a consistent decline in the prevalence of undernutrition among women from 1998 to 2021. The literature has attributed this decline to various reasons like improved awareness, empowerment and education among women (Zajacova and Lawrence, 2018), improvement in Water, Sanitation and Hygiene practices (Kumar and Mohanty, 2023), improved access to healthcare and the impact of nutrition-specific interventions (Joumard and Kumar, 2015; Ahmad et al ., 2023). The role of government initiatives and policies in the reduction of the prevalence of undernutrition among women of reproductive age in India is also documented and is described below: Integrated Child Development Services (ICDS) have been found to have played one of the significant roles in improving the nutritional status and overall development of women and children by providing supplementary nutrition, immunization, health check-ups and pre-school education to pregnant and lactating women (Kapil, 2002).…”
Section: Conclusion and Discussionmentioning
confidence: 99%